ANALISA KINERJA PERBANKAN SYARIAH DI INDONESIA DENGAN MENGGUNAKAN PENDEKATAN ISLAMICITY PERFORMANCE INDEX DAN ISLAMIC CORPORATE GOVERNANCE - Sabirin Sabirin (Fakultas Syariah (Syari'ah Faculty ), 2018)
This research attempts to disclose the implementation of sharia principles in islamic banking performance in Indonesia during 2013-2017 by using Islamicity Performance Index and Islamic Corporate Governance. Purposive sampling technique is used to determine the samples of the research. The samples are 10 Islamic Commercial Banks which their annual report are available in each corporate website. The results of this research show that islamic banking performance in Indonesia is good enough. However, there are two ratios which are less satisfactory, namely zakat performance ratio and director-employee welfare ratio. This shows that zakat which is paid by Islamic banks in Indonesia is still low and there is still a huge gap between directors’ and employees’ welfare.